(untitled) (Linguostylistic Studies, 2014)
Imperative verbs in-up in the texts of Lesya Ukrainka in sahanovsky gorkeho article revealed the formation endings of verbs of the second person plural imperative. Now normative consider inflexion, if the second person singular, the stem ends with a consonant (кинь – киньте), and -іть (неси – несіть). The so-called complete form -іте (ходіте) qualify as obsolete and not recommended for consumption. However, in the works of different writers end up happening, particularly in our fellow Lesya Ukrainka; most often seen in its texts of different genres (poetry, prose, drama, epistolary) were these words: біжіте, візьміте, ждіте, живіте, кладіте, несіте, підіте, робіте, скажіте. It is established that the use of Lesja flexion -іте due to various reasons: to preserve the poetic size, to transfer the solemnity, stylizing the text under national dialects. Verbs ending in -іте are quite common in Dialect of Western Polissya, so the use of this form in the works of the writer reflects folk element. In addition, the identified kind of the actual sahaneasycac contaminatin form ходімте that combines the first and second person plural (ходім + ходіте). The prevalence of the final that led to formation of more of these mandatory forms as нате ‘rent’, гетьте, цитьте that used in the works of our compatriot. Key words: imperative mood, second person plural, works of Lesya Ukrainka, Dialect of Western Polissya. References